Impact of Antibiotics Associated with the Development of Toxic Epidermal Necrolysis on Early and Late-Onset Infectious Complications - Lipovy, Bretislav; Holoubek, Jakub; Hanslianova, Marketa; Cvanova, Michaela; Klein, Leo; Grossova, Ivana; Zajicek, Robert; Bukovcan, Peter; Koller, Jan; Baran, Matus; Lengyel, Peter; Eimer, Lukas; et al. (Microorganisms, 2021)
Toxic epidermal necrolysis (TEN) is a rare disease, which predominantly manifests as damage to the skin and mucosa. Antibiotics count among the most common triggers of this hypersensitive reaction. Patients with TEN are highly susceptible to infectious complications due to the loss of protective barriers and immunosuppressant therapy. The aim of this study was to investigate the potential relationship between antibiotics used before the development of TEN and early and late-onset infectious complications in TEN patients. In this European multicentric retrospective study (Central European Lyell syndrome: therapeutic evaluation (CELESTE)), records showed that 18 patients with TEN used antibiotics (mostly aminopenicillins) before the disease development (group 1), while in 21 patients, TEN was triggered by another factor (group 2). The incidence of late-onset infectious complications (5 or more days after the transfer to the hospital) caused by Gram-positive bacteria (especially by Enterococcus faecalis/faecium) was significantly higher in group 1 than in group 2 (82.4% vs. 35.0%, p = 0.007/p corr = 0.014) while no statistically significant difference was observed between groups of patients with infection caused by Gram-negative bacteria, yeasts, and filamentous fungi (p > 0.05). Patients with post-antibiotic development of TEN are critically predisposed to late-onset infectious complications caused by Gram-positive bacteria, which may result from the dissemination of these bacteria from the primary focus.
Keywords: toxic epidermal necrolysis; late-onset infection; early-onset infection; antibiotics; infectious complication